6.1k views
1 vote
2/-3 divided by -1 2/7 =
pls explain the answer

User KingJinho
by
5.4k points

2 Answers

2 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


(2)/( - 3) / (- 1 (2)/(7)) = \\


- (2)/(3) / ( - ( 7)/(7) - (2)/(7) ) = \\


- (2)/(3) / ( ( - 7 - 2)/(7) ) = \\


- (2)/(3) / ( - (9)/(7) ) = \\

Negatives simplifies


(2)/(3) / (9)/(7) = \\


(2)/(3) * (7)/(9) = \\


(14)/(27) \\

Done...

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Jeffrey Greenham
by
5.8k points
4 votes

Answer:


(14)/(27)

Explanation:


  1. -1(2)/(7) = -(9)/(7)
  2. Plug -9/7 in:
    -(2)/(3) ÷
    -(9)/(7)
  3. -2/3 ÷ -9/7 = 2/3 ÷ 9/7 = 2/3 × 7/9

  4. (2)/(3) ×
    (7)/(9) = (14)/(27)

I hope this helps!

User Moritz Petersen
by
6.0k points